Relationship of changes in SpO2, HR, SpO2/ HR and relativity with those in Hb during altititude training - Ma, S.; Fan, R.; Ma, F. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: The current investigation analyses the changes and the corresponding relationships of SpO2, HR, SpO2/HR and Hb during the morning hours for swimmers after training at an elevation of 2366m. Specifically, this study aimed to explore the possibility of using the first three indices as a way of predicting the results of altitude training and changes in Hb. Methods The subjects of this study were twenty-seven swimmers (11 men and 16 women) aged 16~26y who normally trained at sea-level. The subjects participated in 26 days of high altitude training. Hb, SpO2 and HR were measured in the morning hours through SWELAB AC900EO+ and PM-50 SpO2 testers. The data were analyzed statistically using SPSS (version12.0). Results SpO2 levels decreased and then increased. And in both male and female athletes, SpO2 reached its lowest point on the 5th and 8th days during altitude training (p<0.05) and followed a significant increase at the end of altitude training (men p<0.01, women p<0.05). HR changed inversely to SpO2. In both male and female athletes, it reached its highest point on the 8th and 4th days (p>0.05), and there was a significant decrease at the end of altitude training (p<0.05). The change in SpO2/HR was negatively correlated with HR (p<0.01). In general, the 5th and 9th days are the turning point of Hb; it significantly increased (men p>0.05, women p<0.05), then notably decreased (p<0.01), and subsequently increased significant (p<0.01) at the end of the altitude training. For female athletes, the results showed that SpO2 was negatively correlated with HR (p<0.05) during the adaptation period (from the 1st day to the 8th day), and SpO2/HR was positively associated with SpO2 (p<0.01). Hb was negatively correlated with HR (p<0.05), and Hb was positively related with SpO2/HR (p<0.05) after the adaptation period. For male athletes, there was some correlative tendency between these indexes, but they were not statistically significant. SpO2, HR and SpO2/HR values between male and female athletes had a highly significant distinction (p<0.001). SpO2 and HR were a little higher in female athletes than in male, but the ratio between them was reversed. Conclusions During altitude training, every index changed towards its optimal value, which demonstrates that altitude training was successful and also indicates that the three indices could serve to predict the effectiveness of altitude training similar to the use of Hb. HR and SpO2/HR could be used to predict changes in Hb during altitude training. The difference in SpO2 and relativity of each index between male and female athletes necessitates further research.